Psychological hesitation and willpower and their relationship with the performance of the kinematic chain of the parallel apparatus of different height for third stage students in the College of Physical Education and Sports Science, University of Baghdad - Ameen, Ban Adnan Mohammed; Hasan, Wasan Jasem Mohammed; Liayth, khuloud (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the degree of psychological frequency and willpower and the performance of the kinetic chain on the parallel apparatus of different height for female students as well as to identify the relationship between psychological frequency and willpower and to identify the relationship between psychological frequency and willpower with the level of performance of the kinetic chain on the parallel apparatus of different height.The research community consisted of students of the third stage in the College of Physical Education and Sports Science at the University of Baghdad, and they were (129) students spread over four people and two(63) female students were chosen. (23) female students were excluded from those who did not attend the day of testing. Psychological hesitation, willpower and test in the motor chain in the technical gymnast, and thus the number of the research sample has reached (40) students, i.e. a percentage (31.007) from the research community.The delegation of female researchers using the psychological frequency scale and willpower, then the researchers conducted the scientific foundations of the scale and applied it to the research sample andconducted the test for the kinematic chain. Better, they reached the importance of studying psychological aspects, including willpower, in order to overcome the psychological frequency that you can feel during the performance of your gymnastic skills.